Alleviation of Fatty Liver by Using Soy Proteins in Rat - Nabih, Asmaa; EL-Sherbini , El-Saied; El-Shafei , Reham A.; Salama, Mohamed F. (Journal of Advanced Veterinary Research, 2023)
The purpose of the current investigation is to determine how soy isoflavone (ISF) and genistein (GS) affects oxidative stress, IL1-ß and PPARγ signaling pathways in liver of obese rats and how this pathway is involved in controlling the formation of hepatic fat. The study included 60 male Sprague Dawley rats that were allocated to six groups (n = 10rats) :(I) Fatty liver was induced in rats were daily fed (60% fat energy, high fat diet (HFD)) for 12 weeks ; (II) (Fatty liver + ISF group) rats were daily fed with HFD and 10 mg/Kg ISF intragastrical for 12 weeks ;(III) (Fatty liver + GS group) rats were given HFD and 16 mg/Kg GS in 0.1% DMSO once daily by intragastric tube for 12 weeks; (IV) (Normal control group) rats were fed with normal balanced diet for 12 weeks; (V)(Normal diet + ISF group) rats were fed with normal diet and 10 mg/Kg ISF intragastrical for 12 weeks; (VI) (Normal diet + GS group) rats were fed with normal diet and 16 mg/Kg GS for 12 weeks. All rats allowed water whereas rats got HFD were accompanied by 18% sucrose solution freely. Also, weight was measured weekly. At the end of the experiments lipid profile and liver function were analyzed. Moreover, the levels of MDA, SOD, CAT, and GSH, and the gene expression of IL1-ß and PPARγ genes were detected. Our study showed that fat content was significantly lowered in the liver of ISF and GS -fed obese rats, accompanied by a reduction in hepatocellular vacuolation when compared to the fatty liver control. In ISF and GS fatty liver treated groups SOD, CAT and GSH activities were significantly increased in comparison to the Fatty liver untreated group in addition to that MDA level decreased in ISF and GS groups.IL1-ß expression and PPARγ expressions was dowenregulated in Fatty liver + ISF and Fatty liver+ GS treated rats when compared with Fatty liver one,however the results in Fatty liver+ GS treated rats was significantly Improved over ISF + Fatty liver.Genistein administration alleviated fatty liver through the down-regulation of PPARγ and IL-1 β and up-regulation the activity of oxidative stress marker ( SOD , CAT and GSH).